Effect of Extraction Methods on Chemical Composition, Angiotensin I‐Converting Enzyme Inhibitory and Antioxidant Activity of Coffee Residue. Issue 2 (29th April 2016) - Ben Romdhane, Molka; Krichen, Fatma; Ghazala, Imen; Ellouz‐Chaabouni, Semia; Haddar, Anissa
Abstract: In the present work, polysaccharides were extracted from coffee residue (CRP) using hot water and ultrasound‐assisted extraction methods. Experimental results showed that both CRP had similar monosaccharide compositions (mannose and galactose), they presented also typical IR spectra characteristic of polysaccharides. CRP‐U uronic acid content (6.28 ± 0.93%) was significantly ( P  < 0.05) higher than that of CRP‐H (4.86 ± 0.07%). The ACE inhibitory activities (IC50 CRP‐H  = 0.2 mg/mL and IC50 CRP‐U  = 0.15 mg/mL) and antioxidant capacities of both CRP were assessed via different methods, including DPPH radical‐scavenging activity assay (IC50 CRP‐H  = 0.08 mg/mL and IC50 CRP‐U  = 0.053 mg/mL), reducing power (RP0.5 CRP‐H  = 1.1 mg/mL and RP0.5 CRP‐U  = 0.8 mg/mL), and β‐carotene bleaching inhibition assay (IC50 CRP‐H  = 4.65 mg/mL and IC50 CRP‐U  = 5.59 mg/mL). Those polysaccharides did not show any hemolytic activity towards erythrocytes. Practical Applications: Coffee residue is the major coffee industry residue with an international generation of 6 million tons annually. Taking into account this huge quantity produced worldwide, the reutilization of this residue is a pertinent subject. Results indicated that coffee residue can be used to generate high value‐added products, thus offering a valuable source of polysaccharides for application in wide range of biotechnological and functional food applications.